A Case of Everolimus Related Pneumonitis Occurred After Switching Treatment from Sirolimus in a Kidney Transplant Patient - Kaya, Eda; Karakoç, Alican; Velidedeoğlu, Mehmet; Pekmezci, Salih; Trabulus, Sinan; Seyahi, Nurhan (Cerrahpaşa Medical Journal, 2019)
Pneumonitis is a reported side effect of treatment with mammalian target of rapamycin inhibitors. In this report, we present a case of everolimus-related pneumonitis that occurred after treatment switching from sirolimus to everolimus. A 33-year-old female was admitted to our clinic with fatigue, cough, night sweats, and high fever after treatment switching from sirolimus to everolimus. Thorax CT revealed ground-glass densities and acinar nodules. After withdrawal of everolimus, complete remission was observed. Pneumonitis after treatment switching from sirolimus to everolimus has not been observed before. In patients with pulmonary symptoms during everolimus treatment, drug-related pneumonitis should be considered. Cite this article as: Kaya E, Karakoç A, Velidedeoğlu M, Pekmezci S, Trabulus S, Seyahi N. A Case of Everolimus Related Pneumonitis Occurred After Switching Treatment from Sirolimus in a Kidney Transplant Patient. Cerrahpasa Med J 2019; 43(1): 37-39.